Novel immunotherapy in the management of advanced urothelial cancer - review of the literature - Chmiel, Paulina; Kłosińska, Martyna; Kaczyńska, Agnieszka (Journal of Education, Health and Sport, 2022)
Bladder neoplasms, with the most common urothelial carcinoma, are responsible for approximately 200,000 deaths annually, which is 2.1% of the total cancer deaths in 2018. Recent decades have brought a steadily growing share of this cancer in the statistics. The 5-year survival rate is 77.1% for the United States and it varies depending on the stage of the diagnosed neoplasm, from 96% for cancer in situ to only 5% for the disseminated form with distant metastases. The treatment of urothelial cancer can be divided depending on the stage and advancement. Three main categories of bladder cancer can be distinguished: non-muscle invasive bladder cancer, treated by surgical approaches, and muscle-invasive bladder cancer, treated with chemotherapeutics, lastly advanced bladder cancer with distant metastases, treated with intensive chemotherapy in the MVAC scheme (methotrexate, vinblastine, doxorubicin, and cisplatin). Recently introduced checkpoint inhibitors have revolutionized the treatment of patients with metastatic urothelial carcinoma by increasing patient life expectancy, progression-free survival, and durability of clinical response. This review of the literature will discuss the use of immunotherapy in the treatment of advanced bladder cancer.